FAKTOR PENENTU TINDAK PENGGELAPAN PAJAK: TARIF, KEADILAN, SANKSI PAJAK, DAN TEKNOLOGI INFORMASI - Yustrianthe, Rahmawati Hanny; Pandansari, Sekar Ayu (Universitas Riau Kepulauan, 2025)
This study aims to obtain empirical evidence regarding the influence of information technology, tax rates, tax fairness, tax sanctions on tax evasion. The sample was conducted using a purposive sampling method on individual taxpayers in Yogyakarta as many as 100 respondents. The data collection technique used a questionnaire. The data analysis method used in this study was multiple linear regression. The results of the study indicate that information technology tax rates, tax fairness, and tax sanctions simultaneously have a significant effect on tax evasion, but partially do not have a significant effect.